Botulinum toxin type a combined with transcranial direct current stimulation reverses the chronic pain induced by osteoarthritis in rats. (June 2022) - Li, Xinhe; Ye, Yinshuang; Wang, Lin; Zhou, Wenwen; Chu, Xiao; Li, Tieshan
Abstract: Osteoarthritis (OA) is the most common cause to lead to chronic pain. Sensitization of pain pathways including central sensitization and peripheral sensitization has been regarded as a major cause of OA pain refractory to treatment. Addressing peripheral sensitization or central sensitization alone may not adequately treat OA pain. In our previous studies, botulinum toxin type A (BoNT/A) has been shown to reduce peripheral sensitization for analgesic effects. In addition, transcranial direct current stimulation (tDCS) has also been suggested to reduce central sensitization for analgesia. The present study was designed to investigate whether BoNT/A in combination with tDCS has better analgesic effects than isolated treatment to alleviate OA-induced chronic pain in rats. The Von Frey and hot plate tests were applied to assess the pain-related behaviors at different time points. The expression level of N-methyl-D-aspartate receptor-2B (NMDAR2B) was evaluated in midbrain periaqueductal gray (PAG) by Western blot the Immunohistochemistry staining after different treatments. The results showed that the combined treatment of BoNT/A and tDCS better improved the pain-related behaviors and significantly increased the expression level of NMDAR2B protein in PAG than each isolated treatment. These results suggested that the combined treatments for relief of chronic pain were more obvious than each isolated treatment. The combination of BoNT/A and tDCS may relieve pain by increasing N-methyl-D-aspartate (NMDA) receptors in the PAG, and then the descending inhibitory systems were activated to modulate peripheral and central sensitization. Graphical abstract: Image 1 Highlights: Sensitization of pain pathways has been recognized as a major cause of osteoarthritis pain refractory to treatment. NMDA receptors in midbrain periaqueductal gray play an important role in the relief of chronic pain. Botulinum toxin type A and transcranial direct current stimulation may reduce pain sensitization by NMDA receptors. The combination of botulinum toxin type A and transcranial direct current stimulation provide better analgesic effects. It is important to realize that the treatment of chronic pain should focus more on neurosensitization.